An update of dynamic thermal-hydraulic simulations of the JT-60SA Toroidal Field coil cooling loop for preparing plasma operation. (July 2020) - Varin, S.; Bonne, F.; Hoa, C.; Nicollet, S.; Zani, L.; Vallet, J.-C.; Fukui, K.; Natsume, K.
Highlights: Thermal-hydraulic modelling of cryo-distribution for superconducting magnets. Dynamic simulations of JT-60SA Toroidal Field coil cooling loop. Updated Simcryogenics model with a more accurate thermal model of the magnets. Estimation of the smoothed heat load profiles at the interface with the refrigerator. Abstract: The JT-60SA cryogenic system was commissioned in 2016 in closed loop, without the cryogenic users (superconducting magnets, current leads, thermal shields). The first plasma operation is expected in 2020. This paper updates the heat load profiles resulting from the cooling loop of TF magnets, and received by the refrigerator and its thermal damper. The heat load profiles are calculated through thermal-hydraulic simulations of the magnets and the associated cryo-distribution, also named as supercritical helium loops. This update was performed by taking into account new data from the TF magnets (measured pressure drops, updated heat loads coming from the plasma), as well as a more accurate thermal model of the TF magnet. Previous simulation had been performed using the Vincenta code in 2010 and were used for the cryogenic system acceptance tests. The new thermal-hydraulic model is performed by using Simcryogenics, the modeling tool dedicated to refrigeration and cryo-distribution developed by CEA (Commissariat à l'énergie atomique et aux énergies alternatives). The differences between the two simulation results are highlighted and analyzed. These simulations provide the pulsed heat load profiles smoothed by the cryo-distribution and deposited into the thermal damper.